Resolutions and decisions of the Communist Party of the Soviet Union. - McNeal, Robert, H. (Heritage., 1974)
This set of four volumes is an indispensable reference work for the study of modern Russia in general and Soviet Communism in particular. Volume 3 treats the Stalin era, the early phase of which witnessed a new degree of party intervention in agriculture, industry, and cultural affairs.